2015
DOI: 10.1016/j.jval.2015.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of a Nonpharmacological Intervention in Pediatric Burn Care

Abstract: This economic evaluation showed the Ditto intervention to be highly cost-effective against standard practice at a minimal cost for the significant benefits gained, supporting the implementation of the Ditto intervention during burn wound care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…to an average of 3.2 weeks of treatment with standard care. 1 Similar findings were reported in a recent meta-analysis; although the initial cost of NPWT was higher during treatment, the overall cost was reduced due to the lower costs incurred for personnel-related expenses and the shorter duration of treatment. 6 Augustin et al explored the cost-effectiveness of treating vascular leg ulcers using UrgoStart ® (Urgo Ltd., Loughborough, UK), a hydroactive dressing containing a nano-oligosaccharide factor, and UrgoCell Contact ® (Urgo Ltd.), a neutral foam dressing.…”
Section: E F F E C T I V E N E S Ssupporting
confidence: 86%
See 2 more Smart Citations
“…to an average of 3.2 weeks of treatment with standard care. 1 Similar findings were reported in a recent meta-analysis; although the initial cost of NPWT was higher during treatment, the overall cost was reduced due to the lower costs incurred for personnel-related expenses and the shorter duration of treatment. 6 Augustin et al explored the cost-effectiveness of treating vascular leg ulcers using UrgoStart ® (Urgo Ltd., Loughborough, UK), a hydroactive dressing containing a nano-oligosaccharide factor, and UrgoCell Contact ® (Urgo Ltd.), a neutral foam dressing.…”
Section: E F F E C T I V E N E S Ssupporting
confidence: 86%
“…11 Brown et al compared treatment costs in relation to healing rates and changes in wound size among paediatric burn victims. 1 Wounds treated with single-use negative pressure wound therapy (NPWT) resulted in a marked decrease in wound size, with an average reduction in size of 21% per week. As such, the expense of NPWT was offset by the reduction in wound size, as this form of treatment resulted in wound healing occurring after two weeks compared Table 1: Concept analysis of cost-effectiveness in wound care 1,2,[5][6][7][8][10][11][12][13][14][15][16][17][18][19][20][21] Author and year of publication • Pharmaceutical interventions such as analgaesics and anxiolytic medications also contribute to costs.…”
Section: E F F E C T I V E N E S Smentioning
confidence: 99%
See 1 more Smart Citation
“…We found no published evaluations in burn management using cost-effectiveness modelling. Brown, David et al [23] published an economic evaluation of a distraction-based intervention 'Ditto' in paediatric burn care in Brisbane, Australia based on a small trial (n = 75). The study reported a 95% probability that it was cost-effective compared with standard care, but the results are not easily comparable since they report cost (AU$) per 1-day reduction in re-epithelialization.…”
Section: Summary Of Findings Elsewherementioning
confidence: 99%
“…The most comprehensive economic evaluation currently in the literature of pediatric burn care is an incremental cost-effective analysis examining the use of a non-pharmacological, procedural preparation and distraction intervention (Ditto™) compared to standard practice in the pediatric burns outpatient setting and the effects on wound re-epithelialization [126].…”
Section: Introductionmentioning
confidence: 99%